Subacute toxicity study of hibiscus rosa-sinensis l. leaves water extract in Balb/C mice: biochemical analysis assessment - Ahmad, Siti Salihah (2017)
Hibiscus rosa-sinensis L. is a plant which has been studied for its pharmacological used for a variety of treatment. However, evidence in safety of consumption of this plant is still lacking. This study aimed to investigate the subacute toxicity of H rosa sinensis L. Leaves water extract in BALB/c mice by biochemical assessment as per OECD 407 guidelines. In subacute toxicity study, the extract was dosed at 50, 300 and 2000 mg/kg in both genders for 28 days in 24 mice. Six mice per group consist of three female and three male. For the control group, tap water was given. After 28 days of treatment, the body weights increased in all experimental groups, while for the food consumption was approximately same taken by all the groups within the 28 days. There was no significant different in body weight gain and the food consumption between all groups. Biochemical analysis of hepatic enzymes showed no significant different in aspartate transaminase (AST) and alanine transaminase (ALT). In conclusion, the result indicates no toxicity observed. It suggests that repeated administration of H rosa-sinensis leaves water extract to the highest dose 2000 mg/kg is safe to consume orally by mice for 28 days.